Chronic Invasive Fungal Sinusitis Presenting as Inferior Altitudinal Visual Field Defect. (4th May 2017) - Bansal, Reema; Takkar, Aastha; Lal, Vivek; Bal, Amanjit; Bansal, Sandeep
ABSTRACT: A young male with acute blurring of vision (6/9) complained of an inferior altitudinal field defect in right eye. Clinical ophthalmological examination was normal. Magnetic resonance imaging (MRI) of the brain revealed the expansion and mucosal thickening of right posterior ethmoid and sphenoid sinuses and opacified right maxillary sinus. Surgical intervention (transethmoidal sphenoidotomy) and histopathological examination revealed chronic invasive granulomatous fungal sinusitis. Anti-fungal therapy led to resolution of visual complaints and restoration of visual field defects.